Hematopoietic Cell Kinase (HCK) Is a Player of the Crosstalk Between Hematopoietic Cells and Bone Marrow Niche Through CXCL12/CXCR4 Axis - Roversi, Fernanda Marconi; Bueno, Maura Lima Pereira; Pericole, Fernando Viera; Saad, Sara Teresinha Olalla (Frontiers in Cell and Developmental Biology, 2021)
The crosstalk between hematopoietic stem/progenitor cells (HSC), both normal and leukemic, and their neighboring bone marrow (BM) microenvironment (niche) creates a reciprocal dependency, a master regulator of biological process, and chemotherapy resistance. In acute myeloid leukemia (AML), leukemic stem/progenitor cells (LSC) anchored in the protective BM microenvironment, reprogram and transform this niche into a leukemia-supporting and chemoprotective environment. One of the most important players involved in this crosstalk is CXCL12, produced by the BM mesenchymal stromal cells, and its receptor CXCR4, present onto HSC. The downstream molecular mechanisms involved in CXCL12 / CXCR4 axis have many targets, including the Src family members of non-receptor tyrosine kinase (SFK). We herein study the role of one SFK member, the Hematopoietic Cell Kinase (HCK), in the CXCL12 / CXCR4 pathway and its contribution to the AML pathogenesis. We verified that the inhibition of HCK severely impaired CXCL12-induced migration of leukemic cell lines and CD34 positive cells from AML patients bone marrow, through a disruption of the activation of CXCL12 / CXCR4 / PI3K / AKT and CXCL12 / CXCR4 / MAPK / ERK signaling, and by a decreased cytoskeleton dynamics through a lower rate of actin polymerization. We provide new insights into the key role of HCK in conferring a migratory advantage to leukemic cells through the CXCL12 / CXCR4 axis. HCK represents an important protein of the main pathway involved in the crosstalk between HSC, and their surrounding milieu. Thus, HCK inhibition could represent a novel approach for the treatment of acute myeloid leukemia.